Characterisation of Chemical Compounds from the Root and Leaf Extract of Abrus precatorius - HENRY YUSUFU, WAKAWA; Fasihuddin Badruddin, Ahmad (UNIMAS Publisher, 2023)
A total of five secondary metabolites were isolated and purified from dichloromethane root and leaf extracts of Abrus precatorius using different chromatographic methods. The structures were elucidated using different spectral data and were confirmed to be 5,7-Dimethoxyflavanone (1), Xanthoxylin (2), Hexadecanoic acid (3) successfully isolated from the root extract, and Beta-eudesmol (4) and Squalene (5) successfully isolated from the leaf extract. 5,7-Dimethoxyflavanone (1) and xanthoxylin (2) were reported for the first time from the root extract and this contributed to the pharmacological importance of A. precatorius.